Localized Enhancement of Infrared Radiation Temperature of Rock Compressively Sheared to Fracturing Sliding: Features and Significance - Liu, Xiangxin; Wu, Lixin; Zhang, Yanbo; Mao, Wenfei (Frontiers in Earth Science, 2021)
Previous experiments indicated that infrared radiation temperature (IRT) was applied in monitoring rock stress or rock mass fracturing, and abnormal IRT phenomena preceding rock failure or tectonic earthquakes were frequently reported. However, the characteristics of IRT changing with rock fracturing and frictional sliding is not clear, which leaves much uncertainties of location-and-pattern identification of stress-produced IRT. In this paper, we investigated carefully the localized IRT enhancement of rock compressively sheared to fracturing and sliding (named as CSFS) with marble and granite specimens. Infrared thermogram and visible photos were synchronously observed in the process of rock CSFS experiment. We revealed that localized IRT enhancement was determined by local stress locking, sheared fracturing and frictional sliding, and the relations between the Kcv of IRT and the shear force are almost linear in wave length 3.7-4.8 μm. In the process of rock CSFS, the detected ∆IRT resulted from thermoelastic effect is 0.418 K, while the detected ∆IRT resulted from friction effect reaches up to 10.372 K, which is about 25 times to the former. This study is of potential values for infrared detection of rock mass failure in engineering scale and satellite remote sensing of seismogenic process in regional scale.